A New Series of Ru(II) Polypyridine Surfactants: Synthesis, 2D NMR, Fluorescence, Electrochemistry and Electrochemiluminnescence
A new series of Ru(II) polypyridine surfactants, Ru(bpy)2[phenNHCO(CH2)nCH3](PF6)2, where n is10, 12, 14, or 16, has been prepared and characterized. The 1H-NMR spectra of these new Ru(II) complexes were attributed and discussed by the 1H-1H COSY method. The comparative analysis of IR spectra of these complexes and their responding free ligands has shown that there are intensive d→π* feedback interactions between central Ru(II